(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Up to 13% of people will collapse their nasal valves in their lifetime. Previous rhinoplasty, other surgical procedures, facial paralysis, congenital abnormalities, trauma, and aging are among the etiologies. Collapse of the internal nasal valve impairs nasal breathing, which seriously impairs quality of life. There are numerous methods for expanding the internal nasal valve’s cross-sectional area.